Identifikasi Kualitas Hidup Pada Balita dengan Stunting di Puskesmas Pekauman Kota Banjarmasin : Identification of Quality of Life in Toddlers with Stunting at the Pekauman Community Health Center, Banjarmasin City - Safitri, Ririn; Ariani, Malisa; Fetriyah, Umi Hanik (LPPM STIKES Guna Bangsa, 2025)
Stunting is a malnutrition problem that continues to occur, South Kalimantan is ranked 9th with a prevalence exceeding the national figure. The aim is to determine the quality of life of stunted toddlers at the Pekauman Community Health Center, Banjarmasin City. Descriptive research design. Sample of 30 stunted child respondents using purposive sampling technique. Data collection used the PedsQL questionnaire. The variables studied are quality of life based on physical, emotional, social and school function. Univariate analysis uses mean, median and mode values. Quality of life for physical function (63.3%) was in the good category, mean 78.02. Quality of life for emotional function (56.7%) was in the poor category, mean 67.83. Quality of life for social function (70%) is in the good category, mean 91.00. Quality of life for school functioning (100%) is in the good category, mean 100.00. The results showed that the quality of life with 3 functions was in the good category (59.3%) with a mean value of 77.05. The results of the psychosocial assessment were in the poor category (53.3%) with a mean of 79.41. The conclusion is that the quality of life of stunted toddlers is in the good category. The research contribution is as information for parents that their role is needed in children's growth and development and can be used as discussion material for education regarding regulating the nutritional content of each portion of food for stunted children.